The Legendary Love Story of Qays and Layla: A Comparative Study Between Arabic and Persian Literature (Comprehensive Journal of Science, 2026)
The story of Majnun Layla holds a fixed and established place in Arabic literature, and therefore, whenever chaste love is mentioned, the story of Majnun Layla is mentioned. No story has received the same attention as the story of Majnun Layla. Persian poets also took an interest in it, and many Persian poets composed verses about it, but the one who composed the most was the poet Kanjavi. Kanjavi was greatly influenced by the Arabic narrative, and based on that, there was little change to the story in many aspects in Persian literature. Majnun, who was influenced by Arabic literature, did not change Layla's name, nor the name of Layla, nor the names of Qais's father and Layla's father, and many events came in agreement. This shows that the Persians relied on the Arabic narrative and developed it by adding some elements and linking it to doctrine, such as transforming the story into Sufism, even the title of the story, Layla and Majnun. Thus, the story transitioned from chaste love as it is among the Arabs to divine love among the Persians.